TINGKAT EFEKTIVITAS DAN KONTRIBUSI PAJAK PARKIR TERHADAP PENDAPATAN ASLI DAERAH JOMBANG - POETRI RAHMADHINI, AULIA (Jurnal Akuntansi AKUNESA, 2015)
The aim of the research is todetermine how the levelof effectiveness andthe contribution ofthe parkingtaxto PADtownof Jombang. This research was conductedatthe Departmentof Revenue, Finance, andRegional Asset(DPPKAD) of Jombang. The research methodusesdescriptivemethod. The results showed thateveryyearthe effectiveness andamount of the contributionfluctuate. The highestlevel of effectivenessoccursparking taxin 2013amounted to179.78% and the lowest in 2011 at68.4%. While theparkingtax contributiontowardsthe highestrevenuein 2014amounted to82.17%, while the lowestin 2014amounted to0.01%. Keywords: effectiveness, contribution, parking tax, real district income